If the function $f:\mathbb{R}\to \mathbb{R}$ satisfies $f(x+\pi)=f(\pi-x)=f(x), \forall x \in \mathbb{R}$ then $$\int_0^\infty f(x)\frac{\sin x }{x} \mathrm{d}x = \int _0^\frac\pi2 f(x) \mathrm{d}x$$

How can I prove this equality?

  • $\begingroup$ I believe the function you described doesn't satisfy the condition. $\endgroup$ – user42768 May 1 '14 at 12:58
  • $\begingroup$ @vonbrand surely your $f$ does not satisfy the conditions in the first line of the question. Or have I missed something? $\endgroup$ – David May 1 '14 at 12:58

Indeed, let $$I=\int_0^\infty f(x)\frac{\sin x}{x}dx$$ By asumption $f$ is even and $\pi$-periodic. Moreover, $$\eqalign{ 2I&=\lim_{n\to\infty}\int_{-n\pi}^{(n+1)\pi}\frac{\sin(x)}{x}f(x)dx =\lim_{n\to\infty}\sum_{k=-n}^n\int_{k\pi}^{(k+1)\pi}\frac{\sin(x)}{x}f(x)dx\cr &=\lim_{n\to\infty}\sum_{k=-n}^n\int_{0}^{ \pi}\frac{(-1)^k}{x+k\pi}\sin(x)f(x)dx\cr &=\lim_{n\to\infty}\int_{0}^{ \pi}\left(\sum_{k=-n}^n\frac{(-1)^k}{x+k\pi}\right)\sin(x)f(x)dx\cr &=\lim_{n\to\infty}\int_{0}^{ \pi}U_n(x)f(x)dx\cr } $$ with $$ U_n(x) =\sin(x)\sum_{k=-n}^n\frac{(-1)^k}{x+k\pi} $$ But it is well-known that $\lim_{n\to+\infty}U_n(x)=1$ for every $x\in(0,\pi)$ and that the sequence $\{U_n\}$ is bounded on $[0,\pi]$, so, by the Dominated Convergence Theorem, we conclude that $$ 2I=\int_0^\pi f(x)dx=2\int_0^{\pi/2}f(x)dx. $$ and the desired conclusion follows.

Remark. Concerning the statements about the sequence $\{U_n\}$ these are well-known, and a simple proof can be found here. Indeed, consider $\alpha\in(0,1)$, and let $f_\alpha$ be the $2\pi$-periodic function that coincides with $x\mapsto e^{i\alpha x}$ on the interval $(-\pi,\pi)$. It is easy to check that the exponential Fourier coefficients of $f_\alpha$ are given by $$ C_n(f_\alpha)=\frac{1}{2\pi}\int_{-\pi}^{\pi}f_\alpha(x)e^{-inx}dx=\sin(\alpha\pi)\frac{(-1)^n}{\alpha \pi-n\pi} $$ and since $f_\alpha$ is continuously differentiable on $(-\pi,\pi)$ the Fourier series of $f_\alpha$ converges to $f_\alpha$ on this interval: $$ \forall\,x\in(-\pi,\pi),\quad e^{i\alpha x}=\lim_{n\to\infty}\sum_{k=-n}^{n}C_k(f_\alpha)e^{ikx}=\lim_{n\to\infty}\sum_{k=-n}^{n}\frac{(-1)^k\sin(\alpha\pi)}{\alpha\pi- k\pi}e^{ikx} $$ Taking $x=0$, we get $$ 1=\lim_{n\to\infty}U_n(\alpha\pi) $$

  • $\begingroup$ Thank you. I think you forgot a 1 (the limit of the sequence U). I am sorry, but I can't see the proof of that fact from the relationship given by Parseval's equality in the post that you referred. $\endgroup$ – user42768 May 1 '14 at 17:05
  • $\begingroup$ You do not need Parseval's equality, just that the Fourier series converges at $0$. $\endgroup$ – Omran Kouba May 1 '14 at 17:16
  • $\begingroup$ I do apologize, but I would appreciate it if you could elaborate a little more. $\endgroup$ – user42768 May 1 '14 at 17:25
  • $\begingroup$ I, hope it is clear now. $\endgroup$ – Omran Kouba May 1 '14 at 17:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.